Interação de nanotubo de carbono com poluentes emergentes: um estudo de primeiros princípios - CASTRO, Shuanne Machado (2017)
In this work we study the interaction of the triclosan molecule and 17-α- etynilestradiol molecule in single wall carbon nanotubes (SWCNT) (8,0) and (5,5) through first principles calculations, based in theory of the functional of the density, implemented in the Siesta code. The results show that adsorption of triclosan and 17 α- etynilestradiol modifies the properties of SWCNT (8,0) and (5, 5) and changes in properties depending of adsorption site of the triclosan, the same occurs with 17 ethinyl estradiol. It was observed through the binding energy that triclosan molecule interacts with SWCNT (8,0) through chemical processes in the configurations predicted to more stable with the triclosan molecule was parallel to the axis SWCNT (8,0). Whereas for the molecule of ethinyl estradiol, in the most stable configuration, the interaction occurred through a physical process.The interaction of the triclosan molecule with the nanotube (5.5) in all configurations occurred through a physical process. Whereas, 17 α -ethinylestradiol molecule interacts with the SWCNT (5.5), in the most stable configuration through a chemical process, while in the other configurations the interaction occurred through a physical process. Thus, we propose in this work that SWCNTs are used with a filter device because of reasonable physical interaction with the triclosan molecule and 17 α -ethinylestradiol. In addition, this filter can be reusable, therefore, after filtering, the SWCNTs can be separated from the triclosan molecule.